(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the phenological phases of the wine grape varieties: Oltinday and Rangdor varieties were observed, and the effect of vine bush loading on the phenophases of budding, branch growth, and flowering in these varieties was studied through field observations.